Crack Closure in Cycles with Dwell Times at High Temperature. (1st June 2022) - Garnadt, Florian; Kontermann, Christian; Oechsner, Matthias
Abstract: The growth of short cracks in round bar specimens with a circumferential notch has been investigated by an extensive experimental study. This specific specimen geometry has been applied to determine notch support based on a reduced crack growth rate due to the induced stress gradient compared to situations without a notch. At the same time, this investigation of crack growth in low cycle creep-fatigue conditions reveals a significant influence of dwell times on crack closure, which is discussed in detail in this paper. Therefore, a fracture mechanical approach based on an elastic-(visco)plastic crack growth simulation is used to compute the cyclic effective fatigue and creep crack tip loading. The crack growth rates are then determined by a Paris and Nikbin–Smith–Webster model. All investigations are based on strain controlled conditions at different loading levels. The shape of the applied cycles is trapezoidal, having a dwell time of three minutes at maximum and minimum load, and is symmetric in tension and compression. It turns out that a separate consideration of crack opening and closure reveals an important difference in effective crack tip loading range and therefore has a significant impact on fatigue crack growth. Moreover, this paper shows that the effect of dwell times is linked to the influence on plasticity induced crack closure and to the stress relaxation during the dwell time in compression, yielding less crack closure. Highlights: Impact of creep in dwell times on plasticity induced crack closure. Effectiveness of crack tip loading by cyclic J -Integral. Crack growth simulation with elastic–viscoplastic behavior. Analysis of contact stresses along crack flank. Application and comparison of different crack closure criteria.